Optimizing the Role of Zakat, Infaq, Sedekah, and Waqf (ZISWAF) in Poverty Alleviation in Thailand - Abdullah Abu Bakar; Fatonah Salaeh (Samarinda International Journal of Islamic Studies (SIJIS), 2026)
This study examines the optimization of Islamic social finance—comprising Zakat, Infaq, Sedekah, and Waqf (ZISWAF)—as a strategic instrument for poverty alleviation in Thailand. Despite being a minority-Muslim nation, Thailand possesses significant potential for Islamic philanthropic management, particularly in the Southern provinces. Utilizing a Systematic Literature Review (SLR) following the PRISMA protocol, this research synthesizes academic literature from 2021–2026 to identify the challenges and opportunities in ZISWAF governance. The findings reveal that while Zakat and Waqf institutions contribute to local socio-economic stability, their impact is often hindered by fragmented management, lack of legal integration with national frameworks, and low public digital literacy. The study proposes a "Digital-Integrated ZISWAF Model" to enhance transparency and distribution efficiency. Ultimately, this research provides a roadmap for Thai Islamic institutions and policymakers to leverage social finance for sustainable poverty reduction.